Relationship problems of church and state: conceptual foundations - Биков, Олександр Миколайович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
The article deals with basic conceptual principles of church-state relations in modern Ukraine, the features of church-state relations in independent Ukraine, to determine their importance in the development of civil society.